Pengaruh Celebrity Endorser Dan Product Knowledge Terhadap Purchase Decision Pada Produk Kosmetik Maybelline Dengan Brand Image Sebagai Variabel Intervening di Kota Pekanbaru - Lubis, Pimpy Utami; Kurniawati, Devi (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2023)
This research aims to determine the extent of the influence of celebrity endorsers and product knowledge on the purchase decision of Maybelline cosmetic products, with brand image as an intervening variable in the city of Pekanbaru. The analysis method used in this study involved data collection through questionnaires filled out by female respondents in the city of Pekanbaru who purchased Maybelline cosmetic products. The results obtained from the Partial Test (t-test) are as follows: a) there is a significant influence of celebrity endorsers on brand image, b) there is a significant influence of product knowledge on brand image, c) there is no significant influence of celebrity endorsers on purchase decisions, d) there is a significant influence of product knowledge on purchase decisions, e) there is no significant influence of brand image on purchase decisions, f) brand image cannot mediate the influence of celebrity endorsers on purchase decisions, g) brand image cannot mediate the influence of product knowledge on purchase decisions. Through an Islamic approach, this research attempts to identify values that can be applied in the business context, such as honesty, halalnes, and integrity in the marketing of cosmetic products. By integrating Islamic values into the analysis, it is hoped that this research can provide additional insights into how businesses can be conducted by considering ethical and moral aspects in the context of the cosmetic industry.